2018
DOI: 10.1002/ccd.27480
|View full text |Cite
|
Sign up to set email alerts
|

Robotic‐assisted transradial diagnostic coronary angiography

Abstract: Robotic percutaneous coronary interventions have recently been introduced in the cardiac catheterization laboratory. Robotics offers benefits of greater precision for stent placement and occupational hazard protection for operators and staff. First generation systems were able to advance and retract coronary wires, balloons, and stents, but did not have guide control functions. The second-generation robotic system (CorPath GRX) has an active guide management function offering the ability to move guide catheter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Robot-assisted coronary interventions have recently been developed as an alternative to reduce the reliance on manual operation, [214][215][216][217][218][219][220][221][222][223][224] potentially reducing damage from radiation exposure. 225 Clinical studies have demonstrated the safety and efficacy of the robotic system, which has already been approved for routine application in the US and the European Union.…”
Section: Robotic Angioplastymentioning
confidence: 99%
“…Robot-assisted coronary interventions have recently been developed as an alternative to reduce the reliance on manual operation, [214][215][216][217][218][219][220][221][222][223][224] potentially reducing damage from radiation exposure. 225 Clinical studies have demonstrated the safety and efficacy of the robotic system, which has already been approved for routine application in the US and the European Union.…”
Section: Robotic Angioplastymentioning
confidence: 99%
“…The Corpath robotic system (Corindus, Inc., Natick, MA, USA) allows the interventionist to perform percutaneous coronary intervention (PCI) procedures remotely from the console. The robot-assisted system can synchronously operate a catheter and a guidewire during intravascular surgery [8,9]. The Amigo TM (Catheter Robotics, Inc., Mount Olive, NJ, USA) remote catheter system (RCS) can safely and effectively insert a catheter into the right side of the heart [10].…”
Section: Related Workmentioning
confidence: 99%
“…Corindus, A Siemens Healthineers Company, Waltham, MA, USA). The robotic platform is specifically developed for cardiovascular intervention and enables the manipulation of guidecatheters, 0.014" guidewires, and rapid-exchange interventional devices through a robotic arm (8)(9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Case Presentationmentioning
confidence: 99%